Riesgo químico - toxicológico de adulterantes en la pasta básica de cocaína (PBC) en la unidad médico legal región II - Loreto, 2022 - Paredes Salas, Luis Alberto (2023)
Cocaine use continues to be a high health and cost risk for our society, which can be aggravated by the presence of adulterants. The objective was to determine the chemical-toxicological risk due to the presence of adulterants in the basic cocaine paste, in the Public Ministry Region II-Loreto. The study with quantitative, descriptive, and experimental design, had as population the volume 150 Kg of basic cocaine paste seized in the first semester of 2022 from the provinces of Ramón Castilla and Maynas and was chosen by simple sampling at thirty (30) sampling points, the same ones that were analyzed by infrared spectrophotometry. and the toxicological risk was evaluated in mice inoculated intraperitoneally. The presence of starch (13%) and caffeine (18%) was evidenced as adulterants; and in albino mice, psychostimulant action by cocaine was observed, and in the case of adulteration with caffeine, increased heart rate, hyperactivity, anxiety, restlessness, and seizures were observed.